Myeloperoxidase-Antineutrophil Cytoplasmic Antibody-Negative Microscopic Polyangiitis with Pulmonary Haemorrhage and IgA Nephropathy - Yuichiro Endo; Haruka Minato; Reiko Taki; Mayumi Kato; Satoshi Kore-Eda; Yoshiki Miyachi; Miki Tanioka (Karger Publishers, 2011)
Aim: To report a case of a patient with myeloperoxidase-antineutrophil cytoplasmic antibody (ANCA)-negative microscopic polyangiitis (MPA) and IgA nephropathy associated with severe pulmonary haemorrhage. Case Report: A 59-year-old man presented with ANCA-negative systemic vasculitis accompanied by purpura, nephritis and pulmonary haemorrhage. A skin biopsy specimen revealed pandermal leucocytoclastic vasculitis without IgA deposition and a kidney biopsy showed mesangial nephritis with IgA deposition. Considering these findings, the patient was diagnosed as having MPA with IgA nephropathy. Discussion: In most cases, MPA presents with rapidly progressive necrotizing glomerulonephritis and sometimes lung haemorrhage, while IgA nephropathy is less common among MPA cases. As recent research suggested that in MPA immunoglobulin deposition in the kidney may be an exacerbating factor for renal dysfunction and poor prognosis, close observation is required in these cases.